Pembentukan "Klinik Halal" Dalam Upaya Mewujudkan Halal Industri di Indonesia 2024 - Moh. Adenan; Umi Cholifah; Deasy Wulandari; N. Ari Subagio; Fajar Wahyu Prianto; Susanti Prasetiyaningtiyas; Ririn Irmadayani (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The "Dosen Mengabdi di Desa" Program (Prosendi Desa) is conducted in Tegal Besar Village, Kaliwates District, Jember Regency, which has significant potential for the development of the halal industry towards Indonesia's Halal Industry 2024. The program aims to expedite halal certification for Micro, Small, and Medium Enterprises (MSMEs) by implementing a packaging house concept. The program utilizes the Participatory Rural Appraisal (PRA) approach, involving the collaboration of stakeholders such as government officials, MSME owners, and the Halal Center of UIN KHAS Jember. Through information dissemination, socialization, counseling, and direct assistance, MSME owners are guided in obtaining the necessary business legality in the form of a Business Identification Number (NIB) and Halal Certificate. The solution is divided into two phases. In the first year, efforts include issuing additional NIBs, establishing a "Halal Clinic" in the village, and conducting regular socialization and publications. In the second year, a guidebook for self-declaration halal certification, assistance in registering on sihalal.com, support for field verification and document revisions, and monitoring the certification process are provided. The expected contributions are in two phases. Firstly, by increasing the number of NIBs for MSMEs, the program aims to motivate business owners and bring added value to their activities. Secondly, the establishment of the Halal Clinic aligns with agency theory, addressing human nature, organizational aspects, and information needs. The program's ultimate goal is to ensure a significant number of MSMEs in Tegal Besar Village comply with mandatory halal certification requirements by the end of 2024. This initiative will not only enhance the halal industry but also promote awareness and compliance with halal standards among MSMEs, contributing to the broader goal of Indonesia's Halal Industry in 2024.